PENERAPAN PENDEKATAN DEEP LEARNING TERHADAP PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS IV SD PADA MATERI BANGUN DATAR - Rofi Adnan, Muhammad; Fahriza Fuadiah, Nyiayu; Surmilasari, Nora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The deep learning approach is an instructional method that emphasizes in-depth conceptual understanding, student engagement, and reflective thinking processes. This study aimed to determine the improvement in the mathematical reasoning skills of fourth-grade students regarding the area of ​​squares and rectangles through the implementation of the deep learning approach at SD Negeri 83 Palembang. A pre-experimental research method was employed, specifically the One-Group Pretest-Posttest Design. The research subjects consisted of 23 students from class IV-A. The research instrument was an eight-item essay test that had been validated. The results showed that the average pretest score of 58.61 increased to 78.83 on the posttest. The Shapiro-Wilk normality test indicated that the data were not normally distributed; consequently, the analysis proceeded using the Wilcoxon Signed-Rank Test. The Wilcoxon test yielded an Asymp. Sig. (2-tailed) value of 0.000 (less than 0.05), indicating a significant difference between the pretest and posttest results. Furthermore, the N-Gain analysis showed an average score of 77.19%, falling into the high category. Based on these findings, it can be concluded that the implementation of the deep learning approach effectively improves the mathematical reasoning skills of fourth-grade students regarding the area of ​​squares and rectangles at SD Negeri 83 Palembang.